Strategy for stereospecific characterization of natural triacylglycerols using multidimensional chromatography and mass spectrometry - Kalpio Marika; Linderborg Kaisa M; Fabritius Mikael; Kallio Heikki; Yang Baoru (ELSEVIER, 2022)
Stereoisomeric determination of individual triacylglycerols (TAGs) in natural oils and fats is a challenge due to similar physicochemical properties of TAGs with different fatty acid combinations. In this study, we present a strategy to resolve the enantiomeric composition of nutritionally important TAGs in sea buckthorn (Hippopha & euml; rhamnoides) as an example food matrix. The targeted strategy combines 1) fatty acid profiling with GC, 2) separation of TAGs with RP-HPLC, 3) stereospecific separation with chiral-phase HPLC and 4) structural characterization with MS. Three major asymmetric diacid-and triacid-TAG species were analyzed in sea buckthorn pulp oil. Off-line coupling of RP-HPLC and chiral-phase HPLC allowed separation of several TAG regioisomers and enantiomers, which could not be resolved using one-dimensional techniques. Enantiomeric ratios were determined and specific structural analysis of separated TAGs was performed using direct inlet ammonia negative ion chemical ionization method.Of the TAG 16:0/16:1/16:1 palmitic acid (C16:0) was located predominantly in a primary position and the enantiomeric ratio of TAG sn-16:1-16:1-16:0 to sn-16:0-16:1-16:1 was 70.5/29.5. Among the TAGs 16:0/16:0/18:2 and 16:0/16:0/16:1, only ca 5% had C16:0 in the sn-2 position, thus, ca 95% were symmetric sn-16:0-18:2-16:0 and sn-16:0-16:1-16:0. The enantiomeric ratio of triacid-TAGs containing C16:0 and two unsaturated fatty acids (palmitoleic C16:1, oleic C18:1 or linoleic acids C18:2) could not be resolved due to lack of commercial enantiopure reference compounds. However, it became clear that the targeted strategy presented offer unique and convenient method to study the enantiomeric structure of individual TAGs.(c) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license ( http://creativecommons.org/licenses/by/4.0/ )